2018
DOI: 10.1007/s00436-018-5798-6
|View full text |Cite
|
Sign up to set email alerts
|

A new subtype of Entamoeba gingivalis: “E. gingivalis ST2, kamaktli variant”

Abstract: Entamoeba gingivalis is a protozoan that resides in the oral cavity. Using molecular biology techniques, we identified a novel organism that shares the same ecological niche as E. gingivalis. To differentiate this organism from E. gingivalis, we named it “kamaktli variant.” By sequencing the 18S-ITS1-5.8S-ITS2 rRNA region, we demonstrated that kamaktli variant is 89% identical to E. gingivalis. To elucidate the relationship between kamaktli variant and E. gingivalis, we performed a phylogenetic analysis. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 20 publications
2
30
2
5
Order By: Relevance
“…Indeed, evidence about the kinetics of periodontitis setup is scarce and other possible agents must be considered. First, the ST2 “kamaktli” variant, with a high genetic divergence from E. gingivalis ST1 (Garcia et al, 2018b ) reminds us that strains of parasites may not be equally virulent or may not have the same tropism (Garcia et al, 2018a ). Second, some transcripts from archaea species and viruses are differently abundant between the healthy and the diseased (Deng et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, evidence about the kinetics of periodontitis setup is scarce and other possible agents must be considered. First, the ST2 “kamaktli” variant, with a high genetic divergence from E. gingivalis ST1 (Garcia et al, 2018b ) reminds us that strains of parasites may not be equally virulent or may not have the same tropism (Garcia et al, 2018a ). Second, some transcripts from archaea species and viruses are differently abundant between the healthy and the diseased (Deng et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transcriptomics revealed that E. gingivalis 18s rRNA sequence was detected in all (4/4) periodontal pockets and was less abundant in 60% (6/10), or undetected in 40% (4/10) of healthy sites (Deng et al, 2017 ). Furthermore, genetic variants of E. gingivalis have been identified (Cembranelli et al, 2013 ; Garcia et al, 2018b ) and different levels of virulence reflected at the transcriptomic levels in genetically identical parasites (Santi-Rocca et al, 2008 ) may account for discrepancies in their molecular detection as compared with microscopy or clinical diagnoses. The new clinical characterization of periodontitis (Tonetti et al, 2018 ) will avoid further confusion about the definition of health and various disease grades, that may also be responsible for variability between the studies.…”
Section: Entamoeba Gingivalis and Periodontal Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted July 18, 2020. ; https://doi.org/10.1101/2020.07.16.20155861 doi: medRxiv preprint by assessing the prevalence of the other strain in the future studies (42,54,56). For the negative samples we did not rule out inhibition of PCR completely, which can make our results an underestimation of the true prevalence.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies aimed to investigate parasitic oral colonization among healthy individuals and those with periodontal disease with remarkably variable results (34)(35)(36)(37)(38)(39)(40)(41). Such variability can be related to adoption of different approaches for parasite detection, the existence of previously unknown genetic variants of oral parasites, in addition to limitations of small sample sizes, and possible bias in selection of study subjects among others as reviewed recently (42,43).…”
Section: Introductionmentioning
confidence: 99%